PERKEMBANGAN KEBUDAYAAN AUSTRONESIA DI KAWASAN ASIA TENGGARA DAN SEKITARNYA (THE DEVELOPMENT OF AUSTRONESIAN CULTURE IN SOUTHEAST ASIA AND ADJACENT AREAS) - Theodorus Aries Briyan Nugraha Setiawan Kusuma; Andry Hikari Damai (Balai Arkeologi Kalimantan Selatan, 2019)
Kebudayaan Austronesia menyebar di wilayah Asia Tenggara dan sekitarnya hingga ke kepulauan Pasifik dan Madagaskar. Kebudayaan ini berasal dari Taiwan atau Formosa. Persebaran budaya penutur bahasa Austronesia di Asia Tenggara berpengaruh besar dalam mengembangkan budaya yang masih bertahan sampai masa sekarang. Pengaruh tersebut dapat dilihat pada budaya maritim, budaya pertanian, dan juga dalam aspek-aspek sosial seperti pemujaan terhadap leluhur atau dewa/dewi. Hal ini menjadi penting dalam upaya memperkuat identitas penutur bahasa Austronesia sebagai satu-satunya komunitas yang punya peranan begitu besar di Asia Tenggara. Permasalahan yang diangkat adalah bagaimana proses persebaran penutur bahasa Austronesia dan pengaruhnya dalam kebudayaan di Asia Tenggara. Aspek yang diteliti adalah perkembangan kebudayaan dan masyarakat yang bertutur bahasa Austronesia pada periode 4500-1500 tahun lalu dan penjelajahan Austronesia menyeberangi Samudera Hindia. Metode penelitian ini menggunakan pendekatan deskriptif kualitatif. Teknik pengumpulan data menggunakan studi pustaka dan pengamatan dengan pendekatan metode kualitatif. Penelitian ini membuktikan peranan besar penutur bahasa Austronesia dalam perkembangan kebudayaan di Asia Tenggara. Hasil dari penelitiaan bahwa adanya peranan besar penutur bahasa Austonesia dalam berbagai hal seperti kebudayaan maritim, budaya agraris, ritual penguburan dan juga kepercayaan pada leluhur. Austronesian culture spread out in Southeast Asia and adjacent areas until Pacific Archipelago and Madagascar. This culture came from Taiwan or Formosa. The development of Austronesian speakers has a big influence on develop culture who still survive until now. That influence can be seen in maritime culture, agricultural culture, and social aspects as worship the ancestor or God/Goddess. This thing is important for makes Austronesian speakers stronger as the one and only community who has big part for Southeast Asia culture. The problem is how the process of the spread of speakers of Austronesian languages and their influence in culture in Southeast Asia. The aspect that studied is the development from Taiwan to all regions of Southeast Asia Islands within a period of time 4500-1500 years ago and the exploration of Austronesian crossing the Indian ocean. This research method was conducted using a qualitative descriptive that explain the problem on the object. Data collection techniques with literature review. The data that collected in this research is qualitative. An analysis technique used in this research is a systematic qualitative analysis of Austronesian culture development. The results of the research that their major role Austronesian languages in various things such as technology of boat building, maritime culture, agrarian culture, burial rituals, and belief in ancestors.